THE INFLUENCE OF INTERNAL LOCUS OF CONTROL, EXTERNAL LOCUS OF CONTROL, AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT KEDAUNG SATRYA MOTOR IN SURABAYA - Yudistira Anata Kusuma; Sri Rahayu; Sundjoto; Rifda Fitrianty (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of Internal Locus Of Control, External Locus Of Control, and Compensation on Employee Performance at PT. Kedaung Satrya Motor in Surabaya. The type of research used is quantitative research with an associative approach. The population in this study consists of all employees of PT. Kedaung Satrya Motor in Surabaya, totaling 80 employees, and the entire population was used as the research sample through a census sampling technique. Data collection was conducted through the distribution of questionnaires using a Likert scale, supported by observation and documentation. The data analysis techniques included data quality testing, classical assumption testing, multiple linear regression analysis, partial testing, simultaneous testing, and coefficient of determination testing using SPSS software. The results of the study indicate that Internal Locus Of Control, External Locus Of Control, and Compensation partially have a significant effect on Employee Performance, and simultaneously all three variables have a significant effect on Employee Performance, with Compensation being the most dominant variable.